A nanostructure for enhancing the nonlinear luminescence performance of perovskite and a preparation method thereof

By introducing transparent polymers into perovskites to form nanostructure arrays and adding Fabry-Perot resonator cavity and electrodes to the luminescent layer or substrate, the problem of difficult to create large-area, low-cost, and easy-to-process patterned perovskite nanostructures is solved, and the nonlinear luminescence performance of perovskites is achieved.

CN116948642BActive Publication Date: 2025-03-04SOUTHEAST UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310912185.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-03-04
Estimated Expiration
2043-07-25

AI Technical Summary

Technical Problem

Traditional processes are difficult to manufacture large-area, low-cost, and easy-to-process patterned perovskite nanostructures, and the low stability and nonlinear luminescence performance of perovskites are insufficient, which limits its application in the field of optoelectronics.

Method used

The nonlinear luminescence performance is improved by introducing transparent polymer polymers into perovskites to form nanostructured arrays and adding Fabry-Perot resonator cavity and electrodes to the luminescent layer or substrate.

Benefits of technology

It significantly improves the nonlinear luminescence performance of perovskites, improves its application potential in lasers, wavelength converters, optical logic gates, etc., while reducing production costs and processing complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116948642B_ABST
    Figure CN116948642B_ABST
Patent Text Reader

Abstract

The present invention provides a nanostructure for enhancing the nonlinear luminescence performance of perovskite and a preparation method thereof, comprising a luminescent layer and a substrate arranged in sequence from top to bottom, wherein the luminescent layer of the upper layer is composed of a plurality of independent perovskite nanostructure arrays, and each perovskite nanostructure is a mixture of a transparent high molecular polymer and perovskite. With only a few simple steps, a large-scale nano pattern can be obtained, which has the advantages of low price, easy processing, large-area preparation, etc. In addition, the nanostructure enables the perovskite to obtain an enhanced electromagnetic field, improves the nonlinear optical performance of the perovskite, and lays an important foundation for optoelectronic applications based on micro-nanostructure perovskites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of optoelectronic materials, and in particular to a nanostructure for enhancing the nonlinear luminescence performance of perovskite and a preparation method thereof. Background Art

[0002] In the prior art, all-inorganic halide perovskites (CsPbX3 (X=Cl, Br, I)) are widely used in the optoelectronic field due to their adjustable band gap, narrow full width at half maximum (FWHM), low temperature process and easy synthesis (making them easy to mass produce). (Chem. Eng. J. 393 (2020) 124767; Adv. Mater. 28 (2016) 9163-9168; Nat. Nanotechnol. 17 (2022) 813-816; ACS Nano 12 (2018) 8847-8854). Traditionally, optoelectronic devices use a planar perovskite configuration (arranging and configuring the perovskite material in the form of a planar film). By patterning perovskite planar films into nanoscale structures, their optical properties can be further enhanced or demonstrated to achieve more applications (Nat. Mater. 13 (2014) 451-460; Adv. Opt. Mater. 10 (2022) 2200534). In solar cells, patterning improves efficiency by reducing surface reflectivity, tailored light capture, and higher external radiation efficiency and directionality (Nat. Commun. 7 (2016) 13941; Nano Lett. 16 (2016) 6467-6471). In light emission applications, nanotexturing improves output coupling efficiency and imparts new functions such as directionality and spectral tunability (Nat. Commun. 10 (2019) 727; Adv. Funct. Mater. 27 (2017) 1606525). Another common application of nanopatterning is lasing in one- and two-dimensional distributed feedback (DFB) structures (ACS Nano 11 (2017) 5766-5773).

[0003] However, the low stability of all-inorganic halide perovskites is mainly due to the instability of their lattice structure, and light, oxygen, water, etc. in the environment will accelerate the degradation or phase change of perovskites, further reducing their stability. Therefore, in actual patterning, it is difficult to obtain a stable and efficient conversion rate, which makes the material remain in the research stage. At present, existing studies have proposed several patterning process methods for all-inorganic halide perovskites to improve the conversion rate, which can be roughly classified into: direct patterning method and indirect patterning method. The indirect patterning method is mainly to introduce additional layers, such as polymer layers, and usually uses polyparaxylene or polymethyl methacrylate (PMMA) for patterning lithography technology, which can effectively inhibit the direct contact between perovskite and photoresist. However, the indirect patterning method brings new problems. The method requires a more complex process, which leads to an increase in cost (Adv.Opt.Mater.10(2022)2200534). Direct patterning methods include direct photolithography (ACS Nano 13 (2019) 3823-3829) and inkjet printing (ACS Appl. Mater. Inter. 12 (2020) 22157-22162). Direct photolithography is a traditional method for patterning perovskites. The processing process is relatively cumbersome and complicated, and perovskites are very sensitive to polar solvents (such as water, methanol and acetone) and high temperature environments, because photoresists or polar solvents will inevitably cause the perovskite pattern to collapse, which also makes them generally incompatible with traditional photolithography processes (Adv. Funct. Mater. 27 (2017) 1606525; Light Sci. Appl. 2 (2013) 56). Inkjet printing is the most widely used direct patterning technology for organic and perovskite materials; however, it has limitations in producing high-resolution patterns (Nanoscale 7 (2015) 4423-4431); high resolution of 5 μm has been successfully demonstrated using electrohydrodynamic printing (Adv. Funct. Mater. 29 (2019) 2100857), but further improvement of resolution is difficult to achieve because the nozzle capacity and the single injection volume of the solution cannot be reduced indefinitely (Adv. Funct. Mater. 32 (2022) 0224957). In addition, the low stability of perovskites and the unfavorable balance between optical gain and optical loss in electroluminescent devices make it difficult to realize electrically pumped lasers or laser diodes of perovskites (Nature 617 (2023) 79-85). Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a nanostructure that enhances the nonlinear luminescence performance of perovskite and a preparation method thereof to solve the problem that traditional processes are difficult to manufacture large-area, low-cost, and easy-to-process patterned perovskite nanostructures, and to achieve a significant improvement in nonlinear luminescence performance. The presence of nanostructures in perovskite obtains an enhanced electromagnetic field, improves the nonlinear optical properties of perovskite, and is suitable for lasers, wavelength converters, optical logic gates and other fields.

[0005] Technical solution: A nanostructure for enhancing the nonlinear luminescence performance of perovskite of the present invention comprises a luminescent layer and a substrate arranged in sequence from top to bottom, wherein the upper luminescent layer is composed of a plurality of independent perovskite nanostructure arrays, and each perovskite nanostructure is composed of a mixture of a transparent high molecular polymer and perovskite; when the intrinsic photoluminescence wavelength of the perovskite matches the resonant wavelength generated by the nanostructure array, the nonlinear luminescence performance of the system is significantly improved, and the high molecular polymer not only induces the crystallization of the perovskite, but also plays a role in protecting and stabilizing the perovskite.

[0006] in,

[0007] A Fabry-Perot cavity (FP cavity) can be added to the light-emitting layer or substrate to achieve side lasing or vertical cavity surface lasing.

[0008] Electrodes can be added on both sides and driven by DC or AC to achieve luminescence enhancement or laser.

[0009] The shape of the nanostructure is any one of spherical, yurt-shaped, conical or polygonal.

[0010] The perovskite nanocrystal is a metal halide perovskite having the general formula ABX3, wherein the A-site cation includes MA + (CH3NH3 + ), FA + ([(NH2)2CH] + ) and Cs + ; B position is mainly Pb 2+ , or use different metal ions Sr 2+ 、Zn 2+ 、Ni 2+ , Mn 2+ 、Cd 2+ Sn 2+ 、Co 2+ 、Eu 3+ , Er 3+ , Yb 3+ 、Bi 3+ Partial or complete replacement of Pb 2+ ; X=Cl, Br, I.

[0011] The high molecular polymer is any one of PDMS (polydimethylsiloxane), PMMA (polymethyl methacrylate), PVDF (polyvinylidene fluoride), inorganic (perhydro) polysilazane PHPS n-butyl ether, PVP (polyvinyl pyrrolidone), and photocurable resin.

[0012] The method for preparing the nanostructure for enhancing the nonlinear luminescence performance of perovskite of the present invention specifically comprises the following steps:

[0013] Step 1, the substrate is washed in isopropanol, acetone and ethanol by continuous ultrasonication for 10 to 20 minutes respectively, and then blown dry with nitrogen;

[0014] Step 2, preparing a single-layer nanostructure array master on a substrate;

[0015] Step 3, preparing a polymer mold, using a polymer film to replicate a single-layer nanostructure array master, drying and curing, and then peeling the polymer mold from the substrate, and the obtained mold presents the same size as the single-layer nanostructure array master;

[0016] Step 4, coating a mixture of the perovskite precursor solution and the high molecular polymer on a substrate and patterning it using a polymer mold through a nanoimprint process;

[0017] In step 5, the mold is gently separated from the fixed substrate at the lowest possible rate, and a well-defined nanostructure array pattern has been successfully transferred to the substrate.

[0018] The single-layer nanostructure array master is obtained by any one of traditional photolithography, focused ion beam, laser micromachining, nanosphere self-assembly and inkjet printing.

[0019] The photoluminescence spectra of the nanostructures have wavelengths of 400-500nm, 500-600nm, and 600-700nm, respectively, wherein:

[0020] When the photoluminescence spectrum of the nanostructure is at a wavelength of 400-500nm, BCl2, ACl, BBr2, and ABr powders are weighed in a molar ratio of 1:1:0:0 to 0:0:1:1, and the powders are mixed and pre-dissolved in a DMF solvent to form a perovskite precursor solution with a concentration of 0.01mmol / ml to 0.5mmol / ml and a nanostructure photoluminescence spectrum of 400-500nm;

[0021] When the photoluminescence spectrum of the nanostructure is at a wavelength of 500-600 nm, BBr2, ABr, BI2, and AI powders are weighed in a molar ratio of 1:1:0:0 to 1.8:1.8:1.2:1.2, and the powders are mixed and pre-dissolved in a DMF solvent to form a perovskite precursor solution with a concentration of 0.01 mmol / ml to 0.5 mmol / ml and a nanostructure photoluminescence spectrum of 500-600 nm;

[0022] When the photoluminescence spectrum of the nanostructure is at a wavelength of 600-700nm, BBr2, ABr, BI2, and AI powders are weighed in a molar ratio of 1.8:1.8:1.2:1.2 to 0:0:1:1, and the powders are mixed and pre-dissolved in a DMF solvent to form a perovskite precursor solution with a concentration of 0.01mmol / ml to 0.5mmol / ml and a nanostructure photoluminescence spectrum of 600-700nm.

[0023] The prepared single-layer nanostructure array will generate resonance peaks with resonance wavelengths of 400-500nm, 500-600nm, and 600-700nm to match the nanostructures with intrinsic photoluminescence wavelengths of 400-500nm, 500-600nm, and 600-700nm.

[0024] Beneficial effects: It can be seen from the above that a nanostructure for enhancing the nonlinear luminescence performance of perovskite and a preparation method thereof provided in one or more embodiments of this specification have multiple beneficial effects:

[0025] 1. The traditional patterning process in semiconductors is still photolithography, and perovskite patterning is inevitable in many cases. However, since the traditional photolithography process requires a large amount of solvents and high-energy ultraviolet light exposure, the low stability of perovskites makes their performance easily affected. In addition, the manufacture of micro / nano structures by processes such as electron beam lithography (EBL) and reactive ion etching (RIE) will also face difficulties such as limited processing area, high cost, and complex and time-consuming process design. Nanoimprinting is a non-chemical processing technology; therefore, perovskites no longer face the threat of degradation caused by resists and polar solvents. Here, low-cost, large-scale nanopatterns can be obtained with just a few simple steps.

[0026] 2. Adding a Fabry-Perot cavity (FP cavity) to the light-emitting layer or substrate can realize side lasing or vertical cavity surface lasing. Adding electrodes on both sides and driving by DC or AC can achieve luminescence enhancement or lasing. The architecture has a photonic waveguide composed of an FP cavity and electrodes. The formed lateral optical cavity improves the field confinement in the perovskite gain medium while reducing the optical loss in the charge conduction layer. It also promotes the establishment of amplified spontaneous emission (ASE) due to improved collection of spontaneous seed photons and increased propagation paths in the perovskite medium. Therefore, a large net optical gain is achieved by electrical pumping, and ASE can be presented at room temperature. A Fabry-Perot cavity (FP cavity) can be added to the light-emitting layer or substrate to achieve side lasing or vertical cavity surface lasing. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate one or more embodiments of the present specification or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only one or more embodiments of the present specification. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 is a scanning electron microscope image of the perovskite nanostructure in Example 2;

[0029] Figure 2 is the resonance peak of the perovskite nanostructure in Example 2;

[0030] Figure 3 The nonlinear enhanced photoluminescence spectrum of the perovskite nanostructure in Example 2 was obtained by photoexciting the system using an 800 nm pulsed laser system with a repetition rate of 1 kHz and a pulse width of 120 fs. DETAILED DESCRIPTION

[0031] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with specific embodiments.

[0032] A nanostructure for enhancing the nonlinear luminescence performance of perovskite of the present invention comprises a luminescent layer and a substrate arranged in sequence from top to bottom, wherein the luminescent layer of the upper layer is composed of a plurality of independent perovskite nanostructure arrays, and each perovskite nanostructure is formed by a mixture of a transparent high molecular polymer and perovskite; when the intrinsic photoluminescence wavelength of the perovskite matches the resonant wavelength generated by the nanostructure array, the nonlinear luminescence performance of the system is significantly improved, and the high molecular polymer plays a role in protecting and stabilizing the perovskite while inducing the crystallization of the perovskite. A Fabry-Perot resonant cavity (FP cavity) can be added to the luminescent layer or the substrate to achieve side lasing or vertical cavity surface lasing. Electrodes can be added on both sides, and luminescence enhancement or lasing can be achieved by direct current or alternating current driving. The shape of the nanostructure is any one of spherical, yurt-shaped, conical or polygonal. The perovskite nanocrystal is a metal halide perovskite with the general formula ABX3, wherein the A-position cation includes MA + (CH3NH3 + ), FA + ([(NH2)2CH] + ) and Cs + ; B position is mainly Pb 2+ , or use different metal ions Sr 2+ 、Zn 2+ 、Ni 2+ , Mn 2+ 、Cd 2+ Sn 2+ 、Co 2+ 、Eu 3+ , Er 3+ , Yb 3+ 、Bi 3+ Partial or complete replacement of Pb 2+ ; X=Cl, Br, I. The high molecular polymer is any one of PDMS (polydimethylsiloxane), PMMA (polymethyl methacrylate), PVDF (polyvinylidene fluoride), inorganic (perhydro) polysilazane PHPS n-butyl ether, PVP (polyvinyl pyrrolidone), and photocurable resin.

[0033] Example 1

[0034] A nanostructure for enhancing the nonlinear luminescence performance of perovskite, comprising:

[0035] The light-emitting layer and substrate are arranged in sequence from top to bottom. The upper light-emitting layer is composed of a number of independent perovskite nanostructure arrays, and each perovskite nanostructure is composed of a mixture of transparent high molecular polymer and perovskite.

[0036] A Fabry-Perot cavity (FP cavity) and electrodes are added to the light-emitting layer or substrate to achieve side lasing or vertical cavity surface lasing.

[0037] The substrate can be a quartz sheet, a mica sheet, a silicon sheet, a conductive glass or a flexible material.

[0038] The light-emitting layer is composed of a number of independent perovskite nanostructure arrays. The perovskite nanostructure is a metal halide perovskite with the general formula ABX3, in which the A-site cation includes MA + (CH3NH3 + ), FA + ([(NH2)2CH] + ) and Cs + ; B position is mainly Pb 2+ , or use different metal ions Sr 2+ 、Zn 2+ 、Ni 2+ , Mn 2+ 、Cd 2+ Sn 2+ 、Co 2+ 、Eu 3+ , Er 3+ , Yb 3+ 、Bi 3+ Partial or complete replacement of Pb 2+ ; X=Cl, Br, I.

[0039] The added FP cavity serves as a substrate and forms a Bragg reflection waveguide together with the top electrode, which effectively reduces the light field intensity in the transmission layer, thereby reducing the huge loss caused by the transmission layer. At the same time, the light field intensity in the light-emitting layer gain medium is enhanced to increase the mode gain.

[0040] The added FP cavity and electrodes can be bonded to each other by any of spin coating, thermal evaporation, magnetron sputtering, atomic layer deposition, and electron beam evaporation.

[0041] Example 2

[0042] The method obtains a patterned mold by replicating a single-layer nanosphere master with an original pattern, and then uses the mold to form a perovskite nanopattern through a nanoimprint process;

[0043] Step 1: Substrate preparation;

[0044] The substrate was washed in isopropanol, acetone and ethanol in successive ultrasonic steps of 10 to 20 min, respectively, and dried with nitrogen;

[0045] Step 2: Assembly of two-dimensional dense nanosphere arrays;

[0046] 5 to 20 mL of 1 wt% to 10 wt% 400 nm polystyrene (PS) nanosphere colloidal solution is mixed with 2 to 100 mL of ethanol in a volume ratio and ultrasonicated for 30 to 60 minutes; the PS nanospheres are spread on the water surface by injecting at a speed of 1 to 240 mL / h through a syringe; then, the PS nanosphere monolayer is transferred to a preset substrate by slowly pumping water or raising the substrate; and the nanospheres are tightly attached to the substrate by low-temperature baking (25 to 80° C.);

[0047] Ethanol was added as a dispersant to the water-based PS colloidal solution to reduce the surface tension, thereby making the PS nanospheres more effectively dispersed on the water surface; the amount of ethanol additive depended on the size and concentration of the nanospheres;

[0048] The substrate may be a quartz sheet, a mica sheet, a silicon sheet or a flexible material;

[0049] Step 3: Dry etching the nanosphere array;

[0050] The two-dimensional dense nanosphere array in step 1 is processed by an inductively coupled plasma etcher, and a combination of oxygen and argon gas is introduced (power is 80 to 150 W; gas flow rate is 20 to 50 sccm; time is 18 to 167 s) to obtain a dry-etched nanosphere array;

[0051] Step 4: Preparation of patterned mold;

[0052] Using a polymer film to replicate a single-layer nanostructure array master, drying and curing at 40 to 80° C. for 1 to 24 hours, then peeling the polymer mold from the substrate, the obtained mold presents the same size as the single-layer nanostructure array master;

[0053] The material of the mold in step 4 can be any one of PDMS (polydimethylsiloxane), PMMA (polymethyl methacrylate), PVDF (polyvinylidene fluoride), inorganic (perhydro) polysilazane PHPS n-butyl ether, PVP (polyvinyl pyrrolidone), and photocurable resin.

[0054] Step 5: CsPbBr3 perovskite precursor solution is mixed with polymer;

[0055] A 0.01-0.5 mmol / mL perovskite precursor solution is obtained by dissolving 0.05-1.0 mmol CsBr and 0.05-1.0 mmol PbBr2 in 2-20 mL N,N-dimethylformamide (DMF) solvent, and mixing with 0.1-2 g polymer powder; wherein the solution is stirred at a speed of 800 rpm-1200 rpm for 30 min-60 min;

[0056] The polymer used in step 5 can be any one of PMMA (polymethyl methacrylate), PVDF (polyvinylidene fluoride), inorganic (perhydro) polysilazane PHPS n-butyl ether, PVP (polyvinyl pyrrolidone), and photocurable resin.

[0057] Step 6: Forming CsPbBr3 nanopatterns;

[0058] The CsPbBr3 perovskite precursor solution mixture in step 5 is spin-coated onto the substrate and patterned using a mold through a nanoimprint process. Finally, it is gently separated from the fixed substrate at the lowest possible rate. At this point, the well-defined CsPbBr3 nanopattern has been successfully transferred to the substrate;

[0059] The system was photoexcited using an 800nm ​​pulsed laser system with a repetition rate of 1kHz and a pulse width of 120fs. The photoluminescence (PL) spectrum of the CsPbBr3 nanostructure showed amplified spontaneous emission (ASE) at a lower optical excitation flux in the near-infrared. The amplitude of the PL enhancement can be tuned by changing the resonance produced by the nanostructure. When the resonance is tuned to the intrinsic emission peak of the nanocrystal, the nonlinear luminescence performance of the system is significantly improved. While inducing the crystallization of the perovskite, the polymer also plays a role in protecting and stabilizing the perovskite. This will not only help promote the development of large-area perovskite periodic nanostructures with any configuration, but also pave the way for the further application of perovskite nanostructures in optoelectronic fields such as light-emitting diodes, solar cells and lasers.

[0060] Example 3

[0061] Step 1: Substrate preparation;

[0062] The substrate was washed in isopropanol, acetone and ethanol in successive ultrasonic steps of 10 to 20 min, respectively, and dried with nitrogen;

[0063] Step 2: Assembly of two-dimensional dense nanosphere arrays;

[0064] 5 to 20 mL of 1 wt% to 10 wt% 480 nm polystyrene (PS) nanosphere colloidal solution is mixed with 2 to 100 mL of ethanol in a volume ratio and ultrasonicated for 30 to 60 minutes; the PS nanospheres are spread on the water surface by injecting at a speed of 1 to 240 mL / h through a syringe; then, the PS nanosphere monolayer is transferred to a preset substrate by slowly pumping water or raising the substrate; and the nanospheres are tightly attached to the substrate by low-temperature baking (25 to 80° C.);

[0065] Ethanol was added as a dispersant to the water-based PS colloidal solution to reduce the surface tension, thereby making the PS nanospheres more effectively dispersed on the water surface; the amount of ethanol additive depended on the size and concentration of the nanospheres;

[0066] The substrate may be a quartz sheet, a mica sheet, a silicon sheet or a flexible material;

[0067] Step 3: Dry etching the nanosphere array;

[0068] The two-dimensional dense nanosphere array in step 1 is processed by an inductively coupled plasma etcher, and a combination of oxygen and argon gas is introduced (power is 80 to 150 W; gas flow rate is 20 to 50 sccm; time is 34 to 223 s) to obtain a dry-etched nanosphere array;

[0069] Step 4: Preparation of patterned mold;

[0070] Using a polymer film to replicate a single-layer nanostructure array master, drying and curing at 40 to 80° C. for 1 to 24 hours, then peeling the polymer mold from the substrate, the obtained mold presents the same size as the single-layer nanostructure array master;

[0071] The material of the mold in step 4 can be any one of PDMS (polydimethylsiloxane), PMMA (polymethyl methacrylate), PVDF (polyvinylidene fluoride), inorganic (perhydro) polysilazane PHPS n-butyl ether, PVP (polyvinyl pyrrolidone), and photocurable resin.

[0072] Step 5: CsPbBrI2 perovskite precursor solution is mixed with polymer;

[0073] A 0.01-0.5 mmol / mL perovskite precursor solution is obtained by dissolving 0.017-0.33 mmol CsBr, 0.017-0.33 mmol CsI, 0.034-0.66 mmol PbBr2, and 0.034-0.66 mmol PbI2 in 2-20 mL N,N-dimethylformamide (DMF) solvent, and mixing with 0.1-2 g polymer powder; wherein the solution is stirred at a speed of 800 rpm-1200 rpm for 30 min-60 min;

[0074] The polymer used in step 5 can be any one of PMMA (polymethyl methacrylate), PVDF (polyvinylidene fluoride), inorganic (perhydro) polysilazane PHPS n-butyl ether, PVP (polyvinyl pyrrolidone), and photocurable resin.

[0075] Step 6: Forming CsPbBrI2 nanopatterns;

[0076] The CsPbBrI2 perovskite precursor solution mixture in step 5 is spin-coated onto the substrate and patterned using a mold through a nanoimprint process. Finally, it is gently separated from the fixed substrate at the lowest possible rate. At this point, the well-defined CsPbBrI2 nanopattern has been successfully transferred to the substrate;

[0077] The system was photoexcited using an 800nm ​​pulsed laser system with a repetition rate of 1kHz and a pulse width of 120fs. The photoluminescence (PL) spectrum of the CsPbBrI2 nanostructure showed amplified spontaneous emission (ASE) at a lower optical excitation flux in the near-infrared. The amplitude of the PL enhancement can be tuned by changing the resonance produced by the nanostructure. When the resonance is tuned to the intrinsic emission peak of the nanocrystal, the nonlinear luminescence performance of the system is significantly improved. While inducing the crystallization of the perovskite, the polymer also plays a role in protecting and stabilizing the perovskite. This will not only help promote the development of large-area perovskite periodic nanostructures with any configuration, but also pave the way for the further application of perovskite nanostructures in optoelectronic fields such as light-emitting diodes, solar cells and lasers.

[0078] The morphology and structure were observed using a Hitachi Regulus 8100 scanning electron microscope (SEM). The reflectance spectrum was measured using a Lambda 950 UV / Vis / NIR spectrophotometer. It is clear that when the resonance is tuned to the intrinsic emission peak of the nanocrystal, the nonlinear luminescence performance of the system is significantly improved.

[0079] Overall, the traditional patterning process in semiconductors is still photolithography, and perovskite patterning is inevitable in many cases. However, since the traditional photolithography process requires a large amount of solvents and high-energy ultraviolet light exposure, the low stability of perovskites makes their performance easily affected. In addition, the manufacture of micro / nano structures by processes such as electron beam lithography (EBL) and reactive ion etching (RIE) also faces difficulties such as limited processing area, high cost, and complex and time-consuming process design. Nanoimprinting is a fascinating method because it is a non-chemical processing technology; therefore, perovskites no longer face the threat of degradation caused by resists and polar solvents. Here, low-cost, large-scale nanopatterns can be obtained with just a few simple steps;

[0080] By adding a Fabry-Perot cavity (FP cavity) to the light-emitting layer or substrate, side lasing or vertical cavity surface lasing can be achieved. By adding electrodes on both sides, luminescence enhancement or lasing can be achieved through DC or AC driving. The architecture has a photonic waveguide composed of an FP cavity and electrodes. The formed lateral optical cavity improves the field confinement in the perovskite gain medium while reducing the optical loss in the charge conduction layer. It also promotes the establishment of amplified spontaneous emission (ASE) due to improved collection of spontaneous seed photons and increased propagation paths in the perovskite medium. Therefore, a large net optical gain is achieved by electrical pumping, and ASE can be presented at room temperature. A Fabry-Perot cavity (FP cavity) can be added to the light-emitting layer or substrate to achieve side lasing or vertical cavity surface lasing.

[0081] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of one or more embodiments of the present invention should be included in the scope of protection disclosed by the present invention.

Claims

1. A method for preparing a nanostructure for enhancing the nonlinear luminescence performance of perovskite, characterized in that: The preparation method specifically comprises the following steps: Step 1: The substrate is washed in isopropanol, acetone and ethanol by continuous ultrasonication for 10 to 20 minutes, respectively, and then dried with nitrogen; Step 2, preparing a single-layer nanostructure array master on a substrate; Step 3, preparing a polymer mold, using a polymer film to replicate a single-layer nanostructure array master, drying and curing, and then peeling the polymer mold from the substrate, and the obtained mold presents the same size as the single-layer nanostructure array master; Step 4, coating a mixture of the perovskite precursor solution and the high molecular polymer on a substrate and patterning it using a polymer mold through a nanoimprint process; Step 5, the mold is separated from the fixed substrate, and the well-defined nanostructure array pattern has been successfully transferred to the substrate; The high molecular polymer is any one of polydimethylsiloxane, polymethyl methacrylate, polyvinylidene fluoride, inorganic (perhydro) polysilazane PHPS n-butyl ether, polyvinyl pyrrolidone, and light-curable resin; The preparation method of the perovskite precursor solution is: When the photoluminescence spectrum of the nanostructure is at a wavelength of 400-500 nm, BCl2, ACl, BBr2, and ABr powders are weighed in a molar ratio of 1:1:0:0 to 0:0:1:1, and the powders are mixed and pre-dissolved in a DMF solvent to form a perovskite precursor solution with a concentration of 0.01 mmol / ml to 0.5 mmol / ml and a nanostructure photoluminescence spectrum of 400-500 nm; When the photoluminescence spectrum of the nanostructure is at a wavelength of 500-600 nm, BBr2, ABr, BI2, and AI powders are weighed in a molar ratio of 1:1:0:0 to 1.8:1.8:1.2:1.2, and the powders are mixed and pre-dissolved in a DMF solvent to form a perovskite precursor solution with a concentration of 0.01 mmol / ml to 0.5 mmol / ml and a nanostructure photoluminescence spectrum of 500-600 nm; When the photoluminescence spectrum of the nanostructure is at a wavelength of 600-700 nm, BBr2, ABr, BI2, and AI powders are weighed in a molar ratio of 1.8:1.8:1.2:1.2 to 0:0:1:1, and the powders are mixed and pre-dissolved in a DMF solvent to form a perovskite precursor solution with a concentration of 0.01 mmol / ml to 0.5 mmol / ml and a nanostructure photoluminescence spectrum of 600-700 nm; The perovskite is a metal halide perovskite having the general formula ABX3, wherein the A-site cation is MA + (CH3NH3 + ), FA + ([(NH2)2CH] + ) or Cs + ; B position is Pb 2+ , or use different metal ions Sr 2+ 、Zn 2+ 、Ni 2+ , Mn 2+ 、Cd 2+ Sn 2+ 、Co 2+ 、Eu 3+ , Er 3+ , Yb 3+ 、Bi 3+ Partial or complete replacement of Pb 2+ ; X = Cl, Br or I.

2. The preparation method according to claim 1, characterized in that: The nanostructure includes a light-emitting layer and a substrate arranged in sequence from top to bottom, the light-emitting layer is composed of a plurality of independent perovskite nanostructure arrays, each perovskite nanostructure is formed by a mixture of transparent high molecular polymer and perovskite; the intrinsic photoluminescence wavelength of the perovskite can match the resonant wavelength generated by the nanostructure array; a Fabry-Perot resonant cavity is arranged on the light-emitting layer or the substrate to realize side lasing or vertical cavity surface lasing; electrodes are arranged on both sides of the nanostructure, and luminescence enhancement or lasing is realized by direct current or alternating current driving; the shape of the nanostructure is any one of spherical, yurt-shaped, conical or polygonal.

3. The preparation method according to claim 1, characterized in that: The single-layer nanostructure array master is obtained by any one of traditional photolithography, focused ion beam, laser micromachining, nanosphere self-assembly and inkjet printing.

4. The preparation method according to claim 1, characterized in that: The prepared single-layer nanostructure array will produce resonance peaks with resonance wavelengths of 400 ~ 500 nm, 500 ~ 600 nm, and 600 ~ 700 nm to match the nanostructures with intrinsic photoluminescence wavelengths of 400 ~ 500 nm, 500 ~ 600 nm, and 600 ~ 700 nm.

Citation Information

Patent Citations

  • Micro lens, micro lens array and preparation method

    CN113406733A